2012
DOI: 10.1017/jfm.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

Collapse and pinch-off of a non-axisymmetric impact-created air cavity in water

Abstract: The axisymmetric collapse of a cylindrical air cavity in water follows a universal power law with logarithmic corrections. Nonetheless, it has been suggested that the introduction of a small azimuthal disturbance induces a long term memory effect, reflecting in oscillations which are no longer universal but remember the initial condition. In this work, we create non-axisymmetric air cavities by driving a metal disc through an initially-quiescent water surface and observe their subsequent gravity-induced collap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…There are evidences 15,17,[19][20][21] supporting that for some initial conditions, the interface develops high curvature regions followed by re-entrant water fingers. Using simulations with boundary integral method, I found that, starting with one single mode perturbation, there .…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…There are evidences 15,17,[19][20][21] supporting that for some initial conditions, the interface develops high curvature regions followed by re-entrant water fingers. Using simulations with boundary integral method, I found that, starting with one single mode perturbation, there .…”
Section: Introductionmentioning
confidence: 81%
“…For experiments studying the collapse of a non-axisymmetric, impact-created air cavity in water [19][20][21] , the initial length scale (∼ cm) is larger compared with bubble breakup experiments while the initial velocity scale there is similar (∼ m/s). Hence for cavity collapse experiments, if the curvature singularity were to form, air compressibility will be the major mechanism to regularize the curvature singularity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And we marginally expect cavities in the regime of low Reynolds and small Bond numbers. Apart from spheres, the impact of discs has also been studied (Bergmann et al 2010), as well as non-axisymmetric objects (Enriquez et al 2010(Enriquez et al , 2012.…”
Section: Introductionmentioning
confidence: 99%